How Students Choose Careers: Understanding the Career Choices, Motivations and Problems of Agricultural Students in Anambra State, Nigeria - Enibe, D. O.; Ndubisi, U. F.; Egbe, F. N. (American International Journal of Social Science Research, 2020)
The study accessed agricultural undergraduate students’ reasons for choosing agriculture as a career, sources of their motivation, and problems encountered in their study. Data were collected through a structured questionnaire administered on 100 respondents selected through simple random sampling process from two Faculties of Agriculture of two universities: Chukwuemeka Odumegwu Ojukwu University (COOU) and Nnamdi Azikiwe University (NAU) both in the Anambra State of Nigeria. Some of the information provided by the respondents was verified through 4 in-depth interviews. Descriptive statistics such as percentage, frequency distributions, and Tables were used in analyzing the data. The result show that the majority of the students of COOU (48%) and NAU (44%) study agriculture through a constriction (admission offer outside their original career choice) and that the students’ parents were their major source of motivation (64%). The result further reveals that financial constraints (48%), unfavorable government policy (24%), and poor teaching aids were the major problems of agricultural undergraduate students in the State. The study concludes that sustainable involvement of youths in agricultural development is a felt need which requires diversified motivation attention. The study recommends proactive measures such as intermittent rewards and scholarship awards to agricultural students, early stimulation of student’s interest in agriculture, formulation of suitable agricultural policy and provision of adequate teaching facilities and aids to agricultural students by the Universities Management and their Visitors, Nongovernmental Organizations in agriculture and Philanthropists.